Tradisi Ruwatan Murwakala Anak Tunggal dalam Tinjauan Sosiokultural Masyarakat Jawa - Setiawan, Eko (Prodi Sosiologi Agama, 2018)
The tradition of ruwatan children as one of the traditional Javanese heritage is still preserved. Ruwatan is a purification to overcome or avoid an inner difficulty by way of performing wayang kulit by taking the murwakala or sudamala. The tradition of ruwat anak tunggal is the tradition of throwing away the sengkala or bad luck that existed in a single child. In the process of tradition, ruwat is usually done first beginning with a leather puppet performance. The Ruwatan tradition as part of Javanese customs is a tradition of a traditional heritage that is still believed to be a means of disposing of sengkala or bad luck in a single child.